Hubungan tingkat pengetahuan terhadap perilaku penggunaan antibiotik pada mahasiswa medis di Universitas Malahayati - Kirana, Dhea Ananda; Nofita, Nofita; Feladita, Niken (JOURNAL OF Pharmacy and Tropical Issues, 2024)
Background: Antibiotics were the main drugs used as anti-bacterial or infection. Improper use of antibiotics would result in the emergence of adverse antibiotic resistance. One of the high risk factors for resistance was the lack of knowledge about antibiotic drugs. Lack of knowledge resulted in inappropriate antibiotic use behavior. The purpose of this study was to determine the level of relationship between knowledge and behavior in the use of antibiotics among medical students at Malahayati University, namely Medical, Midwifery and Nursing students. This research was conducted using an online questionnaire and statistically analyzed with the Spearman Test. The results of the study indicated that the level of knowledge of the majority of medical students at Malahayati University was in the category of good knowledge with a percentage of 85.50% and the majority of antibiotic use behavior was included in the category of moderate behavior with a percentage of 55.90%. Spearman's analysis shows that respondents' knowledge and behavior have a significant relationship with a significance of 0.003 correlation coefficient of 0.452 which indicates the correlation strength relationship is in the moderate or not strong and not weak category, the direction of the correlation is positive (+) which means that there is a significant relationship between the knowledge of Medical Students at Malahayati University on the behavior of using antibiotics. Purpose: Improve the quality of knowledge on the use of antibiotics in medical students at Malahayati University Method: research using a questionnaire sheet and purposive sampling Result: knowledge has an alpha value of 0.599 and a questionnaire about antibiotic use behavior has an alpha value of 0.527 where both are in the range of 0.50-0.70 values. Conclusion: The level of knowledge of Medical Students about antibiotics, the majority are in the category of good knowledge.   Keywords: Use of Antibiotic Drugs; Knowledge level; Behavior Level.   Pendahuluan: Antibiotik merupakan obat utama yang digunakan sebagai anti bakteri atau  infeksi. Penggunaan antibotik yang tidak benar akan berakibat munculnya resistensi antibiotik yang merugikan. Salah satu faktor tingginya resiko resistensi adalah rendahnya ilmu pengetahuan mengenai obat antibiotik. Rendahnya ilmu pengetahuan menhasilkan perilaku penggunaan antibiotic yang tidak benar. Tujuan dalam penelitian ini yaitu untuk mengetahui tingkat hubungan pengetahuan terhadap perilaku penggunaan antibiotik dikalangan mahasiswa Medis di Universitas Malahayati, yaitu pada Mahasiswa Kedokteran, Kebidanan dan Keperawatan. Penelitian ini dilakukan dengan quisioner online dan dianalisis statistika dengan Uji Spearman. Hasil dari penelitian menunjukkan bahwa  tingkat pengetahuan Mahasiswa medis di Universitas Malahayati mayoritas termasuk dalam kategori pengetahuan baik dengan persentase sebesar 85,50% dan Perilaku penggunaan antibiotik mayoritas termasuk dalam kategori perilaku cukup dengan persentase sebesar 55,90%. Analisis Spearman menunjukkan pengetahuan dan perilaku responden memiliki hubungan yang bermakna dengan signifikansi sebesar  0,003 koefisien korelasi sebesar 0,452 yang menandakan hubungan kekuatan korelasi dalam kategori moderat atau tidak kuat dan tidak lemah, arah korelasi positif (+) yang artinya terdapat hubungan yang signifikan antara pengetahuan Mahasiswa Medis di Universitas Malahayati terhadap perilaku pengguaan  antibiotik. Tujuan: Meningkatkan mutu pengetahuan pengunaan penggunaan antibiotik pada mahasiswa medis di Universitas Malahayati Metode: Penelitian menggunakan lembar kuisioner dan purposive sampling Hasil: Pengetahuan memiliki nilai alpha sebesar 0,599 dan kuesioner tentang perilaku penggunaan antibiotik memiliki nilai alpha sebesar 0,527 dimana keduanya berada pada rentang      nilai 0,50-0,70. Simpulan: Tingkat pengetahuan Mahasiswa Medis tentang antibiotik, mayoritas termasuk dalam kategori pengetahuan baik.   Kata Kunci : Penggunaan Obat Antibiotik; Tingkat Pengetahuan; Tingkat Perilaku.